Aggression and hierarchical steepness inhibit social play in adult wolves - Cordoni G.; Palagi E. (Behaviour, 2015)
In canids, play dynamics seem to be more affected by dominance hierarchy rather than cooperative social bonds. To test this hypothesis we studied a colony of grey wolves (Canis lupus lupus). We quantified the dynamics of aggression and hierarchical changes in two periods (Sample 1 and Sample 2). Sample 2 was characterized by higher level of aggressiveness and by a more strict and steep linear hierarchy. The negative correlation between rank distance and play frequency characterizing both periods and the higher play asymmetry in Sample 2 suggest that rank rules dictate play rules thus highlighting the competitive side of wolf play behaviour. The overall affiliation rates showed no variation between the two samples. Yet, play performance was modified. In Sample 2, wolves reduced playful activity, limited the number of players per session and avoided playing during high competition contexts. Our findings support the hypothesis that wolf play is modulated by dominance relationships more than by cooperative social bonds.